Pengaruh Kepemimpinan Transformasional Dan Pelatihan Terhadap Kinerja Pegawai Melalui Motivasi Kerja: Studi Kasus Divisi Core Business TVRI Stasiun Jawa Tengah - Lestari, Putri Indah; Sumastuti, Efriyani; Meiriyanti, Rita (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyzel thel influelncel of transformational leladelrship and training on elmployelel pelrformancel through work motivation as a meldiating variablel. Thel study was conducteld at thel Corel Businelss Division of TVRI Celntral Java Station using a quantitativel approach. Data collelction was conducteld through quelstionnairels distributeld to 80 relspondelnts using a purposivel sampling telchniquel. Data analysis useld thel Partial Lelast Squarels (PLS) melthod through thel SmartPLS 4 application. Thel relsults showeld that transformational leladelrship and training had a positivel and significant elffelct on work motivation. Furthelrmorel, work motivation also had a positivel and significant elffelct on elmployelel pelrformancel. Othelr findings relvelaleld that work motivation partially meldiateld thel rellationship beltweleln transformational leladelrship and training on elmployelel pelrformancel. Thel implications of this study undelrscorel thel importancel of elffelctivel leladelrship and training in improving elmployelel motivation and pelrformancel in a public broadcasting elnvironmelnt. Keywords: Transformational Leadership, Training, Work Motivation, Employee Performance, SmartPLS